Delisting of firms in Malaysia; what the financial conditions and auditor reports reveal? - Raza, Ali; Wan Hussin, Wan Nordin; Abdul Majid, Jamaliah (Advances in Social Sciences Research Journal, 2019)
The study examines the financial conditions and auditor’s reports in relevance with the delisting of firms from the Malaysian stock market. The dataset comprised of the period of 5 years from 2012 to 2016 and finds out that total 69 companies were delisted from the exchange. By using the descriptive and univariate analysis techniques we find out that poor financial condition is a major reason of delisting of firms in Malaysia. The mean difference between unclean and clean audit opinion groups demonstrate that auditor’s role to evaluate the going concern assumption is also very important as more then 1/3 of the firms received unclean audit opinion due to going concern uncertainty. The unclean group delisted firms on average showed high losses, high negative ROA, high leverage and low total assets as compared to clean group. The study is useful for investors and other stakeholders to make their investing decisions efficiently.